Kişiselleştirilmiş Bir Akıllı Ulaşım Bilgilendirme Sistem Önerisi - GÜZELCİ, ORKAN ZEYNEL (The Turkish Online Journal of Design Art and Communication, 2015)
Nowadays, with technological developments and the popularization of mobile communication devices Advanced Traveler Information Systems become more popular for people who are traveling in the city. When Advanced Traveler Information Systems analyzed, in general, it is possible to see that systems produce monotype and not personalized route suggestions. These monotype routes ignore many parameters involved in the transportation process. Transportation activity has a complex structure that is affected by many physical and non-physical parameters varies from one to another. In the study, this complex structure is described through the transportation system of Istanbul. As a result of examination with a critical point of view, the necessity of a new Advanced Traveler Information System in Istanbul's Urban Transportation is highlighted. For more realistic route alternatives that consider all parameters and personal preferences affecting the transport infrastructure of the city, a conceptual framework of a new Advanced Transportation Information System developed.
Keywords: Akıllı Ulaşım Bilgilendirme Sistemleri; Çok Modlu Ulaşım; Rota Belirleme; Kullanıcı Alışkanlıkları; Coğrafi Etiketleme; Advanced Traveler Information System; Multimodal Transportation; Route Planning; User Routines; Geotagging